Ireland - politics with some social bases - an interpretation based on survey data - Laver, Michael (Economic & Social Studies, 1986)
Following on from the analysis of aggregate data on party choice in Ireland published in the last issue, this paper reports a re-analysis of a ten-year series of commercial opinion polls. The small sample sizes of the commercial polls yield even smaller numbers in social subcategories of the electorate, a problem dealt with by applying mathematical smoothing techniques to the series of polls, in order to remove unwanted sampling `noise?. Trends emerge much more clearly as a result of this, and the social bases of support for the parties are easier to discern. In contrast to the results of the aggregate analysis, the Fine Gael vote exhibits clear social patterning. The Labour vote is also patterned, while the Fianna Fail vote is the least obviously affected by the socio-economic variables used in the opinion polls. Comparing the results of the aggregate and survey analyses, it appears that the scale of the social patterning of voting behaviour differs between Fine Gael and Fianna Fail, with Fine Gael voting affected by factors that vary within local areas and Finna Fail voting affected by factors that vary between them.
Keywords: Election analysis - Ireland; Political parties - Ireland